Ultrasound Evaluation of Normal Thyroid Size - Basnet, Prabhat; Kumar Singh, Ashutosh; Upadhyay, Hari Prasad; Chaulagain, Rajib (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Normal thyroid size determination is very important for the accurate diagnosis of various thyroid disease. There are different thyroid pathologies which lead to increase in size of the thyroid gland, therefore it is essential to know the accurate dimension of the thyroid gland. This study was aimed to evaluate the normal range of thyroid gland dimensions. Methods The study was a descriptive cross-sectional study conducted on 115 patients, in Department of Radiology and Imaging, College of medical sciences, Bharatpur, Nepal. All ultrasound examinations were performed using Toshiba Aplio 500 superficial probe. The data was analyzed using Statistical Package for the Social Sciences (SPSS) version 16 (SPSS, Inc., an IBM Company, Chicago, IL). Descriptive statistics was used to analyze the data. Results Among the 115 patients who participated in the study, 24 (20.9%) were male and 91 (79.1%) were female. The mean length of the right lobe was more (3.67±0.338 mm) than in the left lobe (3.45±.423 mm). The overall mean volume of thyroid gland was 6.71±2.05 ml. The mean volume of thyroid gland in males was 7.91±2.91 ml and in females was 6.40±1.63 ml. Conclusions The present study estimated the normal dimension of thyroid gland. The normal dimension of thyroid gland volume was found to be more in male than in female. The mean total volume was found to be similar to the earlier published study from Nepal.